INCOME DISTRIBUTION AND FOOD SECURITY OF FARM HOUSEHOLD IN SLEMAN DISTRICT, YOGYAKARTA - Jangkung Handoyo Mulyo; Sugiyarto Sugiyarto (UPT Penerbitan Universitas Jember, 2012)
The objectives of the study are to 1) identify the income distribution among farm households, 2) identify food security of farm household level, and 3) analyze the determinants of farm household food security in Sleman district. The study was conducted in Depok and Godean sub districts, Sleman district. The location was chosen purposively by considering its characteristic. Depok subdistrict represents sub urban area, whileGodean subdistrict represents rural area. Sixty five farm households was interviewed at random. The Gini ratio was applied to measure the equality of income distribution among households. The Jonsson and Toole clasification of food security was used to identify the farm household food security. An ordinal logistic regression model was employed to analyze the determinants of farm household food security. The study shows 1) the onfarm income is high unequally distributed among farm households, 2) farm household are less secure 46.2 percent, secure 33.8 percent, vulnerable 12.3 percent and insecure 7.7 percent, 3) the determinants of farm household food security are the price of rice, price of sugar,family size, off farm income and asset.